PEMBELAJARAN KEWIRAUSAHAAN BERBASIS PENGALAMAN LAPANGAN: STUDI KUNJUNGAN MAHASISWA KE JAPRI COFFEE - Abiseka Sahal Rizky Fauzi; Alfin Husna Ridho Pangestu; Filzah Aulia Filzah Aulia (Media Resonansi Pengabdian Masyarakat, 2025)
This article aims to explore the dynamics of entrepreneurship in the Micro, Small, and Medium Enterprises (MSMEs) sector through a field learning approach based on direct interviews with business actors. The object of study in this research is Japri Coffee, an MSME founded by alumni of the Muhammadiyah University of Jakarta. Interviews with business owners reveal various important aspects in managing a micro business, from the establishment process, business model development, to survival strategies amidst limited resources. Japri Coffee shows that entrepreneurial practices do not always depend on complex managerial structures, but rather on innovative capabilities and flexibility in facing operational challenges. Simple marketing strategies such as word of mouth and the use of social media are part of the adaptation that is relevant to the youth market segment. On the other hand, the transition from manual financial recording to the use of simple software shows that business actors are aware of the importance of more structured financial management. Through this field learning, students gain an empirical understanding of the characteristics and real challenges faced by MSMEs in carrying out entrepreneurial activities sustainably.Keywords: Entrepreneurship, UMKM, Field learning, Japri Coffee, Students